2012
DOI: 10.1021/jf301674u
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Fermentation of Soybean and Corn Processing Coproducts for Potential Feed Improvement

Abstract: Two agro-industrial coproducts, soybean cotyledon fiber and distiller's dried grains with solubles (DDGS), were used as substrates to evaluate the effect of coculturing three different fungi, Aspergillus oryzae, Trichoderma reesei, and Phanerochaete chrysosporium, on enzyme production by solid-state fermentation (SSF). When soybean fiber was used as the substrate, a maximum xylanase activity of 757.4 IU/g and a cellulase activity of 3.2 IU/g were achieved with the inoculation and incubation of T. reesei and P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…used in this study for the biofilm development has been tested individually for their nutritional content as an animal feed supplement . There are reports suggesting the feed quality will improve if fermented in a solid state process by Aspergillus oryzae, Trichoderma reesei, and Phanerochaete chrysosporium . It was found that the fermented product had 3.5 − 15.1% lower fiber and 1.3 − 4.2% higher protein contents, suggesting a potential feed quality improvement .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…used in this study for the biofilm development has been tested individually for their nutritional content as an animal feed supplement . There are reports suggesting the feed quality will improve if fermented in a solid state process by Aspergillus oryzae, Trichoderma reesei, and Phanerochaete chrysosporium . It was found that the fermented product had 3.5 − 15.1% lower fiber and 1.3 − 4.2% higher protein contents, suggesting a potential feed quality improvement .…”
Section: Resultsmentioning
confidence: 98%
“…The protein in the co‐products is generally metabolized by fungi or algae and is converted to biomass proteins, which can be harvested easily and can be a rich source of protein. The solid‐state fermentation of soybean and corn processing coproducts showed a marginal increase in the protein content, due to the concentrating effect caused by microorganisms metabolizing the substrates . The end product of protein degradation is mostly NH 3, which is a preferred nitrogen source for algal growth .…”
Section: Resultsmentioning
confidence: 99%
“…It has also been used as a substrate in solid-state fermentation for production of arachidonic acid (ARA) and eicosapentaenoic acid (EPA) (Lio and Wang, 2013). Lio and Wang (2012) demonstrated solid-state fermentation using lignocellulose-degrading fungi to improve digestibility of IF.…”
Section: Introductionmentioning
confidence: 99%
“…According to the estimation of Royal Dutch/Shell group renewable resources could supply 30% of the worldwide chemical and fuel needs, resulting in a biomass market of $150 billion by the year 2050 [60,61].…”
Section: Agrobiotechnological Processmentioning
confidence: 99%